Exploring Students’ Difficulties in LMS-Based English Reading Learning: A Case Study - Sri Arfani (Jurnal Pembelajaran Bahasa dan Sastra, 2026)
The aim of the research is to examine more deeply the students' experiences regarding students' difficulties in learning to read English based on the Learning Management System (LMS). This research was carried out at the English Literature Study Program, Bina Sarana Informatika University (UBSI) Jakarta, which was carried out in the odd semester of the 2025-2026 academic year. The research approach uses qualitative with a case study design. Data collection techniques are interviews, observation and documents. Data analysis consists of data reduction, data presentation and drawing conclusions. The findings concluded that the primary difficulty for students learning English reading lies in interacting with the LMS to improve reading comprehension. Several challenges were identified in using an LMS in the classroom, including understanding linguistic context, pedagogical design features in the LMS, technical barriers to accessing the LMS, student reading and learning strategies, and the role of lecturers in interacting with students